Aroclor 1254 causes atrophy of exocrine pancreas in mice and the mechanism involved. Issue 6 (20th November 2014) - Lin, Moudan; Wu, Tian; Sun, Lingbin; Lin, Jackie Jin; Zuo, Zhenghong; Wang, Chonggang
ABSTRACT: Polychlorinated biphenyls (PCBs) are a class of organic pollutants that have been linked to pancreatic disease. However, their role in affecting the exocrine function of pancreas and the underlying mechanism remains elusive. In the present study, male C57 mice were treated with Aroclor 1254, a commercially available PCBs mixture, at a dosage of 0.5, 5, 50, or 500 μg kg −1 every 3 days by oral gavage. Decrease in pancreas/soma index and acinar atrophy were observed in the mice after exposure for 50 days. Aroclor 1254 exposure significantly decreased the PCNA‐positive cells in the pancreatic acini in a dose‐dependent manner. In addition, western blot analysis showed that PCNA expression was decreased in pancreas in the presence of Aroclor 1254, which suggests that Aroclor 1254 suppresses cell proliferation. TUNEL‐positive apoptotic cells as well as the expression of Bcl2, BclXL, BAX, and Bad of exocrine pancreas did not show significant changes in the treated mice, indicating that Aroclor 1254 has no effect on apoptosis. We also found that phosphorylation of ERK1/2, P90RSK1 and Bad was increased in the treated groups; this compensatory activation of phosphorylation in ERK1/2‐P90RSK1‐Bad signaling cascade could protect cell from apoptosis to maintain the cell numbers and function of exocrine pancreas. Moreover, we found that the expression of Kras and TNFα was increased in the pancreas, indicating that Aroclor 1254 exposure could result in increased risk of inflammation and carcinoma. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 671–678, 2016.